Avian forebrain processing of magnetic intensity and inclination: hippocampus, anterior forebrain Wulst and an unexpected double-dissociation. Issue 3 (4th May 2021) - Bingman, Verner P.; Pemberton, Merissa L.; Mora, Cordula V.
Abstract : It is often neglected that the ability of birds to extract navigational information from the earth's magnetic field can be shaped by learning and memory, which would necessarily recruit brain regions of the telencephalon that support cognitive processes. In the current study, we exploited a validated, conditioning experimental paradigm to explore the possible role of the homing pigeon hippocampal formation (HF) and anterior forebrain Wulst in the detection of variation in both magnetic field intensity and inclination. Whereas HF lesions resulted in a complete loss of intensity discrimination while sparing inclination discrimination, Wulst lesions had the opposite effect, resulting in a complete loss of inclination discrimination while sparing intensity discrimination. It is not surprising that Wulst lesions should disrupt inclination discrimination because in migratory songbirds, regions of the Wulst are known to support the geomagnetic compass, which relies on inclination. More challenging is explaining why HF should be sensitive to variation in magnetic intensity. We suggest that the observed HF sensitivity to intensity may reflect incorporation of geomagnetic irregularities (anomalies) as pigeons learn a map-like representation of familiar landmarks and landscape features. The parallel processing of magnetic intensity and inclination in the homing pigeon forebrain sets the foundation for future studies designed to better understand how cognitive processing can influence geomagnetically guided navigational behavior in birds.